Group size of cynomolgus macaque (Macaca fascicularis Raffles, 1821) in Banyumas Regency, Central Java, Indonesia: A review - Rosyid Ridlo Al Hakim; Erie Kolya Nasution; Rizaldi Rizaldi; Siti Rukayah (SAINSMAT: Journal of Applied Sciences, Mathematics, and Its Education, 2022)
The cynomolgus macaque (Macaca fascicularis) is a primate species that socially lives in many adult males and females. The number of individuals in each troop (group size) is different. Long-tailed macaque habitats were found in several locations in Banyumas Regency, reported to be in Mount Slamet, Cikakak-Wangon, Kalisalak-Kebasen, and the Dieng Mountains. This review article will explain the group size of long-tailed macaques whose habitat is in several Banyumas Regencies, Central Java, Indonesia. The results are in a group size of long-tailed macaque in Banyumas Regency varied and consisted of several troops. Further research is needed to determine the cause of the distribution of long-tailed macaques found in several areas in Banyumas Regency, Central Java, Indonesia.